LncRNA NEAT1 protects uremic toxin-induced intestinal epithelial barrier injury by regulating miR-122-5p/Occludin axis - Meng Han; Pathuama P; Jinhai Tian; Chen Wang; Shengnan Zhou; Lina Fu; Libin Wang; Na Tian (PLoS ONE, 2025)
Background Long non-coding RNA(LncRNA) has been reported to be associated with intestinal barrier damage. The aim of this study was to explore the mechanism of lncRNA Nuclear enriched abundant transcript 1 (NEAT1) in uremic toxin-induced intestinal epithelial barrier injury. Methods Human colon cancer cells (Caco-2) were used to establish intestinal epithelial injury models with the urea treatment in different conditions. Cell Counting Kit-8 (CCK-8) and Western blot screening the best concentration and time. The expressions of lncRNA NEAT1 and miR-122-5p were measured by quantitative real-time polymerase chain reaction (qRT-PCR). Western blot and immunofluorescence were used to detect the expression of tight junction proteins Occludin, ZO-1 and Claudin-1. Sodium fluorescein was used to detect the paracellular permeability of intestinal epithelial injury models. The binding of miR-122-5p to lncRNA NEAT1 and Occludin was determined by bioinformatics analysis and dual luciferase reporter assay. Results The best condition for the injury model was urea treatment in 144 mg/dl for 48 hours. With the increase of urea intervention time and concentration, the damage degree of intestinal epithelial cells is aggravated. Based on the qRT-PCR results, lncRNA NEAT1 was significantly down-regulated in the model group. Meanwhile, the tight junction proteins Occludin, ZO-1 and Claudin-1 were significantly reduced. The permeability of sodium fluorescein was significantly increased in the model group. Overexpression of lncRNA NEAT1 can alleviate the above performances. As the target gene of lncRNA NEAT1, miR-122-5p is significantly up-regulated in the model group. The dual luciferase reporter assay proved that miR-122-5p was targets to Occludin. The protective effect of overexpression lncRNA NEAT1 on intestinal epithelial barrier function is reversed by miR-122-5p mimics. Conclusion LncRNA NEAT1 protects uremic toxin-induced intestinal epithelial barrier injury by regulating miR-122-5p/Occludin axis.